Quantification of viable protozoan parasites on leafy greens using molecular methods - Kim, Minji (2021)
Protozoan contamination in produce is of growing importance due to their capacity to cause illnesses in consumers of fresh leafy greens. Viability assays are essential to accurately estimate health risk caused by viable parasites that contaminate food. We evaluated the efficacy of reverse transcription quantitative PCR (RT-qPCR), propidium monoazide coupled with (q)PCR, and viability staining using propidium iodide through systematic laboratory spiking experiments for selective detection of viable Cryptosporidium parvum, Giardia enterica, and Toxoplasma gondii. In the presence of only viable protozoa, the RT-qPCR assays could accurately detect two to nine (oo)cysts/g spinach (in 10 g processed). When different proportions of viable and inactivated parasite were spiked, mRNA concentrations correlated with increasing proportions of viable (oo)cysts, although low levels of false-positive mRNA signals were detectable in the presence of high amounts of inactivated protozoa. Our study demonstrated that among the methods tested, RT-qPCR performed more effectively to discriminate viable from inactivated C. parvum, G. enterica and T. gondii on spinach. This application of viability methods on leafy greens can be adopted by the produce industry and regulatory agencies charged with protection of human public health to screen leafy greens for the presence of viable protozoan pathogen contamination.